HUBUNGAN ANTARA MOTIVASI DAN KEBIASAAN BELAJAR DENGAN HASIL BELAJAR BIOLOGI - Nur Amaliah; Nurhidayah Nurhidayah; Phika Ainnadya Hasan; Masyitha Wahid (JURNAL BIOEDUKASI, 2022)
Motivation and good study habits are two things that are needed by every student in achieving maximum learning results. This research is a correlation study which aims to determine (1) the relationship between motivation and students' biology learning outcomes, (2) the relationship between students' biology habits and learning outcomes, and (3) the relationship between motivation and study habits and students' biology learning outcomes. The population is 144 people and the sample is 59 people from class XII IPA MAN 1 Polewali Mandar. Data on motivation and study habits were collected using a questionnaire while data on learning outcomes was collected through documentation. The results showed that students' learning motivation was included in the high category (54.24%), study habits were included in the moderate category (67.79%) and learning outcomes were included in the sufficient category (54.24%). The results of the correlation test showed that there was no relationship between motivation and study habits with the biology learning outcomes of class XII IPA MAN 1 Polewali Mandar students (P 0.05).